Sosialisasi Penerapan Biosecurity Sebagai Upaya Pencegahan Penularan Penyakit Pada Ternak Kerbau - Arnold Ismael Kewilaa; Yulina Tiwery; Ary S. lekiohapy; Windy Sopla; Marlisye Laitera; Wasti Yakobus; Ellen F. Kaidara; Ino F. Kuara; Dina Meikudy; Mersi Y. Aitiawasima; Evi Marisa Korleru; Marlista Dolwoy; Gresia D. Keiwury; Gresya Sairtory (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
The aim of this activity is to provide understanding to buffalo breeders regarding the importance of implementing biosecurity in preventing disease transmission in livestock, increase breeders' awareness of biosecurity measures that must be taken in the livestock environment, and equip breeders with practical knowledge about ways to prevent disease through implementation of biosecurity. This activity was carried out using an outreach method involving the community and the Head of Syota Hamlet and his staff. The methods used in this activity are: Material Presentation and Interactive Discussion. Some common biosecurity applications are access control, animal movement control, cleanliness and sanitation, waste management, health monitoring and vaccination. This socialization activity was successfully attended by around 35 people in the program target area. Most breeders showed an increased understanding of the importance of implementing biosecurity after following the socialization. Farmers claim to be ready to implement biosecurity measures such as quarantining new livestock, managing livestock waste, and providing good sanitation in the livestock environment. Some farmers also asked for further assistance regarding more specific biosecurity implementation, such as how to properly vaccinate livestock. In this socialization, several biosecurity measures were emphasized to be applied to buffalo livestock, including: quarantine of new livestock, cleanliness of pens and the environment, prevention through vaccination, waste management, protection of workers and visitors.